(3eNJUQ Pjd GdJbjjO aj eYQaI QhGI GdSff hGdeSGfjOs - (3CHi YeQGf ceGd GdOjf ehSi Hf CMeO GdUQjai GdPDGdis; (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecj GdMSfj,J (B832 (3g` s
(3ChdgG (B:s
(3bGd GdbGVi Jbi GdOjf eMeO Hf CMeO GdbGSi gcPG cJGH LeYJg ai ef YdeJg hbO bUQJ ef gPG GdPjd hGNJUQJg dfaSi aMPaJ efg LejY CSeGA QLGdg s
(3BNQgG (B:s
(3JhajJ HGdbOS SfI GKfJi YTQI hSHY eFI ai LeGOi GdChdi dgG SJ hKeGfhf SfI Je eNJUQ Pjd GdJbjjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3hGdJbjjO dGHf fbWI GdMfHdi GdHZOGOi SfI (B629s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs